2024
DOI: 10.1186/s13293-024-00622-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sex biases in gene expression and sex biases in autism and Alzheimer’s disease

Stuart B. Fass,
Bernard Mulvey,
Rebecca Chase
et al.

Abstract: Background Sex differences in the brain may play an important role in sex-differential prevalence of neuropsychiatric conditions. Methods In order to understand the transcriptional basis of sex differences, we analyzed multiple, large-scale, human postmortem brain RNA-Seq datasets using both within-region and pan-regional frameworks. Results We find evidence of sex-biased transcription in many autosoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
0
0
Order By: Relevance
“…Similarly, our analysis of the human GTEx data showed that female-biased genes were enriched for microglial markers (OR = 4.607, p adj = 0.003) and endothelial markers (OR = 17.233, p adj < 0.001) ( Table S8 ), although sex differences in SPVs were only significant for endothelial cells ( p adj < 0.001) ( Figure 3 D; Table S9 ). These findings are consistent with (1) previous analyses of the human GTEx data, 45 (2) the presence of a neurodevelopmental gene co-expression module in postnatal human brains that is enriched for both microglial markers and female-biased genes (ME3), 46 (3) reports of female-biased microglial proportions in adult humans, 47 and (4) our finding that human-macaque conserved female-biased genes (LMM p adj < 0.05 and mashr β < 0; n = 1,105 genes; STAR Methods ) were enriched for immune-related biological processes ( g:Profiler p adj < 0.05) ( Figure 3 E; Tables S10 – S12 ). This shared pattern may reflect evolved sex differences in immune surveillance and response due to the need for birthing people to tolerate an internal, immunologically challenging pregnancy.…”
Section: Resultssupporting
confidence: 93%
“…Similarly, our analysis of the human GTEx data showed that female-biased genes were enriched for microglial markers (OR = 4.607, p adj = 0.003) and endothelial markers (OR = 17.233, p adj < 0.001) ( Table S8 ), although sex differences in SPVs were only significant for endothelial cells ( p adj < 0.001) ( Figure 3 D; Table S9 ). These findings are consistent with (1) previous analyses of the human GTEx data, 45 (2) the presence of a neurodevelopmental gene co-expression module in postnatal human brains that is enriched for both microglial markers and female-biased genes (ME3), 46 (3) reports of female-biased microglial proportions in adult humans, 47 and (4) our finding that human-macaque conserved female-biased genes (LMM p adj < 0.05 and mashr β < 0; n = 1,105 genes; STAR Methods ) were enriched for immune-related biological processes ( g:Profiler p adj < 0.05) ( Figure 3 E; Tables S10 – S12 ). This shared pattern may reflect evolved sex differences in immune surveillance and response due to the need for birthing people to tolerate an internal, immunologically challenging pregnancy.…”
Section: Resultssupporting
confidence: 93%